Tunka-Grande and TAIGA-Muon scintillation arrays: status and prospects. (December 2020) - Monkhoev, R; Astapov, I; Bezyazeekov, P; Borodin, A; Brueckner, M; Budnev, N; Chernykh, V; Chiavassa, A; Dyachok, A; Fedorov, O; Gafarov, A; Garmash, A; et al.
Abstract: The Tunka-Grande and TAIGA-Muon arrays are the part of a single experimental complex, which also includes the Tunka-133 and TAIGA-HiSCORE (High Sensitivity COsmic Rays and gamma Explorer) wide-angle Cherenkov arrays, TAIGA-IACT array (Imaging Atmospheric Cherenkov Telescope) and Tunka-Rex radio antennas array (Tunka Radio Extension). This complex is located in the Tunka Valley (Buryatia Republic, Russia), 50 km from Lake Baikal. It is aimed at investigating the energy spectrum and mass composition of charged cosmic rays in the energy range 100 TeV - 1000 PeV, searching for diffuse gamma rays above 100 TeV and studying local sources of gamma rays with energies above 30 TeV. This report outlines 3 key points. The first is a description of the Tunka-Grande and TAIGA-Muon scintillation arrays. The second part presents preliminary results of the search for diffuse gamma rays with energies above 50 PeV according to the Tunka-Grande data. The third part is devoted to the prospects of the search for diffuse gamma rays with energies above 100 TeV using the TAIGA-Muon array.